2018
DOI: 10.1021/acs.molpharmaceut.8b00522
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Natural Compound Radicicol as a Potent FTO Inhibitor

Abstract: The fat mass and obesity-associated protein (FTO), as an mA demethylase, is involved in many human diseases. Virtual screening and similarity search in combination with bioactivity assay lead to the identification of the natural compound radicicol as a potent FTO inhibitor, which exhibits a dose-dependent inhibition of FTO demethylation activity with an IC value of 16.04 μM. Further ITC experiments show that the binding between radicicol and FTO was mainly entropy-driven. Crystal structure analysis reveals tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 45 publications
0
58
0
Order By: Relevance
“…Our previous results showed that radicicol, CHTB, and N‐CDPCB can bind to FTO. It was found that CHTB‐FTO complex has the highest binding affinity followed by 1d, radicicol, and N‐CDPCB as shown in Table .…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Our previous results showed that radicicol, CHTB, and N‐CDPCB can bind to FTO. It was found that CHTB‐FTO complex has the highest binding affinity followed by 1d, radicicol, and N‐CDPCB as shown in Table .…”
Section: Resultsmentioning
confidence: 96%
“…Enzymatic activity assays in vitro were carried out as described previously . Analogues at varying concentrations (3.0 μM, 6.0 μM, 10.0 μM, 15.0 μM, 30.0 μM, 50.0 μM, 100.0 μM, and 150.0 μM) were used in the assays.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations